China-Kazakhstan Energy Relations After the Cold War (2022)
Energy has maintained its importance for humanity since the ancient periods of history to this day. This importance has increased with the increasingly dependence of industrial development on the use of energy. As a matter of fact, the value loaded into energy over time has also been discussed with different dimensions. At the point reached today, energy forms part of national security. It is also indisputable that it will maintain this position in the future, as it did yesterday and today. The issue of energy security is now being considered in the national security dimension for all parties that need or hold this resource. In this aspect, it is not only a security issue that concerns nations, but also the focus of attention of the international system. In this aspect, the aspect of energy security that connects states in international relations stands out. Our study considers the concept of energy security through Kazakhstan and China and emphasizes different aspects of this concept within the two countries. The energy views and challenges of the two countries are presented within the framework of the concept of energy security and emphasis is placed on developing relations.